Change-Oriented Risk Management in Civil Aviation Operation: A Case Study in China Air Navigation Service Provider. (28th May 2020) - Yuan, Le-ping; Liang, Man; Xie, Yiran
Abstract : Change-oriented risk management is the key content of civil aviation safety management. Hazard identification is considered as one of the most difficult and flexible parts. To address the risk management due to changes introduced in existing systems, in this paper, a system change-oriented hazard identification (SCOHI) model is firstly proposed. The SCOHI model identifies hazards by integrating "5M" (mission-man-machine-management-medium), and hazard and operability (HAZOP) techniques specify changes in a system and the associated impacts on the surrounding environment. Compared with the traditional brainstorm process, the SCOHI model provides an explicit way for hazard identification in a dynamic environment. Then, taking an air navigation service provider (ANSP) in Northwest China as an example, a case study of system changes from nonradar control operations to radar control operations is analyzed. The effectiveness and applicability of the SCOHI model are tested with a risk assessment. The results from the preliminary evaluation show that the four key system change-oriented hazards are air traffic control (ATC) skills, staff capacity, control procedures, and airspace structure. In addition, the "Man" category accounts for around 55% of the total risk, ranking number 1, followed by "Management, " "Medium, " and "Machine" categories. Finally, a sound risk control strategy is provided to the ANSP to help in controlling the risk and maintaining an acceptable level of safety during system changes.